Sintesis Hidroksiapatit Dari Kulit Kerang Darah Dengan Metode Hidrotermal Suhu Rendah - Muhara, Ikhbal; Fadli, Ahmad; Akbar, Fajril (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Synthesis of hydroxyapatite from sea shells has been successfully done by the low temperature hydrothermal method. The purpose of research is to determine the effect oftemperature calcination and holding time on the hydroxyapatite properties. Firstly, sea shells were calcined at 1000°C for 24 hours for producing CaO. And then 55.63 grams of (NH4)2HPO4 was dissolved in 600 mL of distilled water and then 45.91 grams of CaO added into the solution until formed a slurry. Subsequently, the slurry was dried in an oven at 120°C for 15 hours. The drued slurry was crashed and calcined at temperature of 700°C, 800°C, 900°C, 1000°C and holding time of 0.5 hours, 1 hour, 1.5 hours and 2 hours. The results showed that the diameter of the crystal at the temperature calcinationof 700°C is 52.87 nm, while the diameter of the crystal at temperature of 800°C is 52.17 nm. The diameter of the crystal at temperature of 900°C and 1000°C are 51.32 and 50.09nm respectively. Functional groups of PO4 3- and OH are detected in the obtained hydroxyapatite.Keywords: Hydroxyapatite, Hydrothermal, Sea Shells and Crystal Diameter